A parsimonious macroeconomic ABM for labor market regulations - Caner Ates; Dietmar G. Maringer (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
The literature on macroeconomic agent-based models (MABMs) has gained growing attention since the early 2000s. Most MABMs dealing with market regulations have been focusing on the financial market. In contrast, only a small number of MABMs investigate the effects of labor market regulations. In this paper, we provide a parsimonious yet extendable agent-based model that focuses on labor market dynamics within a macroeconomic framework, suitable to analyze labor market regulations such as minimum wages and employment protection legislations. The model is stock-flow-consistent and small-scaled, i.e., there are only workers and firms interacting in the goods and in the labor market. There are two different types of workers, namely skilled and unskilled, and firms produce according to a CES production function. This allows for substitutability between the two types of workers. A one-factor-at-a-time (OFAT) sensitivity analysis is performed to gain insights into the mechanisms and patterns produced by the model. Results show that the model is sensitive to the minimum wage parameter and that for reasonable values of the minimum wage, income inequality decreases, while aggregate consumption rises. Overall, the results suggest that the model can be used to further investigate aggregate and distributional effects of labor market regulations.
Keywords: E24; C63; 330; Labor market; minimum wage; stock-flow consistent; macroeconomic agent-based model; CATS